Kemasan Alternatif Patung Garuda Dari Bali - Zulfa Humam (Jurnal Kimia dan Kemasan, 1998)
Garuda Carving Statue from Bali is one of Indonesian Handicraft export comodity. Folding and Corrugated Carton have been designed as a packaging materials used for Garuda Carving Statue as a retail and transport packaging respectively.The properties evaluated in this experiment are thickness and gramage for retail packaging material ; and flute, bursting and edge Crush Tester for transport packaging material.The Best Result is Folding Carton with thickness= 0,66 mm, gramage 467,74 gr/m'' and Corrugated.Carton with flute B, Bursting= 8,64 kgf/cm", ECT = 6,68 kgN/m.